Rate enhancement in palladium catalyzed Heck reactions by Lewis acid promoters - Sud, Abhishek; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Significant enhancement in the rate of Heck reactions has been achieved when catalytic amounts of Lewis acid (like FeCl(3)) promoters in the presence of trace amounts of water (> 2000 ppm) are used along with Pd complex catalysts. Experiments with different aryl halides, bases as well as olefins have been carried out to demonstrate the role of Lewis acid promoters. The increase in the reaction rates is due to the weakening of Ar-X bond by the Lewis acid in the manner similar to Friedel-Crafts reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Heck reaction; Lewis acid; Palladium; Promoters

Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.